Hubungan antara penguasaan literasi sastra dan minat belajar dengan kemampuan menulis cerita anak pada peserta didik kelas iv sekolah dasar - Sugara, Ujang; Slamet, St Y; Budiharto, Tri (Didaktika Dwija Indria, 2021)
This study aims to determine (1) whether there is a relationship between mastery of literary literacy and  write children’s story; 2) the relationship of interest to learn with the ability to write children’s story; (3) the relationship between mastery literary literacy and interst to learn with the ability to write children’s story. The method used is the survey correlational method. The sample is 4 elementary schools, totaling 112 students. Data collection using tests and questionnaires. The ability to write children story is used in the form of a composing test instrument, an instrument of interest to learn used in the form of a questionnaire, mastering literary literacy of data variables obtained with choice test. Data were analyzed using simple correlation and multiple correlation analysis. The results showed that (1) there was a significant relationship between literary literacy mastery with the ability to write children storyr rcount (0,98)> rtable (0,192), the correlation coefficient tested by t test, the results of tcount (65,08)> ttable (1.98); (2) there is significant the relationship between interest to learn and write children story ability price r count (0,99)> r table (0,185), the correlation coefficient is tested by t test, the ttcount (65.08)> Table (1.98); (3) there is a significant correlation between literary literacy and interest to learn together with the ability to write narration. ry (1,2) equal to 0.97, the coefficient of significance with the F test obtained F count = 27517.35, the real level á = 0, 05, with df 109 obtained Ftable = 3.08 then Fcount> Ftable. Thus, it can be concluded that mastery of literacy and interest of learn has significant relationship with students' ability to write children story.